2020
DOI: 10.1016/j.isci.2020.100859
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-Based Signals Regulate the Assembly of Daple⋅PARD3 Complex at Cell-Cell Junctions

Abstract: Polarized distribution of organelles and molecules inside a cell is vital for a range of cellular processes and its loss is frequently encountered in disease. Polarization during planar cell migration is a special condition in which cellular orientation is triggered by cell-cell contact. We demonstrate that the protein Daple (CCDC88C) is a component of cell junctions in epithelial cells which serves like a cellular ''compass'' for establishing and maintaining contact-triggered planar polarity. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 52 publications
(72 reference statements)
3
24
0
Order By: Relevance
“…A notable feature of the C-terminal PBM on GIV-L is its highly conserved sequence, which, like that in Daple (Figure 3A), includes two tyrosine residues. Those sites in Daple serve as substrates for multiple tyrosine kinases and their phosphorylation has been shown to modulate PDZ•PBM interactions with ParD3 and Dvl ( Figure 4A) (Aznar, Midde et al 2015, Ear, Saklecha et al 2020. In coimmunoprecipitation experiments between GIV-L and ParD3, we observed a specific interaction between GIV-L and the third PDZ domain on ParD3 (Figure 4B), mirroring exactly what was shown previously for Daple (Ear, Saklecha et al 2020).…”
Section: Multiple Pdz Proteins Bind the Pbm On Giv-l And Modulate Gα-supporting
confidence: 85%
See 4 more Smart Citations
“…A notable feature of the C-terminal PBM on GIV-L is its highly conserved sequence, which, like that in Daple (Figure 3A), includes two tyrosine residues. Those sites in Daple serve as substrates for multiple tyrosine kinases and their phosphorylation has been shown to modulate PDZ•PBM interactions with ParD3 and Dvl ( Figure 4A) (Aznar, Midde et al 2015, Ear, Saklecha et al 2020. In coimmunoprecipitation experiments between GIV-L and ParD3, we observed a specific interaction between GIV-L and the third PDZ domain on ParD3 (Figure 4B), mirroring exactly what was shown previously for Daple (Ear, Saklecha et al 2020).…”
Section: Multiple Pdz Proteins Bind the Pbm On Giv-l And Modulate Gα-supporting
confidence: 85%
“…CCDC88C/Daple also features a C-terminal PBM motif that is similar but not identical in sequence to that in GIV-L, raising the possibility that GIV-L has a unique PDZ interactome. Analysis of our own BioID proximity labeling studies, and others, reveal that GIV-L indeed binds to several PDZ domain-containing proteins, which only partially overlaps with that of Daple (Ear, Saklecha et al 2020). Interaction assays confirmed that GIV-L and Daple can indeed bind to the some common PDZ-proteins (e.g., ParD3 and Dvl).…”
Section: Ccdc88 Proteins Exemplify Evolutionary Enrichment Of How Pbmmentioning
confidence: 68%
See 3 more Smart Citations